Design of fiber-reinforced soft bending pneumatic artificial muscles for wearable tremor suppression devices. (1st December 2020) - Wirekoh, Jackson; Parody, Nicholas; Riviere, Cameron N; Park, Yong-Lae
Abstract: Soft robotics is a rapidly evolving field offering novel solutions in the development of wearable technologies. Soft pneumatic artificial muscles in particular, have seen widespread use in the development of human scale rehabilitative and assistive wearables. However, these soft actuators have not yet been adapted to address the complex dynamic regime of active (essential tremor) and resting (Parkinson's disease) hand tremor, the most common movement disorder affecting humans. Current solutions to address hand tremor involve expensive medication and surgical interventions, as well as wearable assistive devices that fall short of providing an effective compact design for the suppression of hand tremor. This study focuses on the design of a novel lightweight, compact, bending actuator that will be capable of actively suppressing hand tremor when adapted into an assistive wearable device. The proposed fiber-reinforced bending pneumatic artificial muscle (BPAM), including its design specifications, fabrication process, theoretical modeling, and experimental characterization, are detailed. The developed actuator was capable of producing sinusoidal trajectories with peak-to-peak amplitudes of 40° and a bandwidth of 8 Hz, the dynamic regime of pathological hand tremor. The ability of the fiber-reinforced BPAM to act within the dynamic regime of hand tremor demonstrates its potential to be further developed into a system capable of the active suppression of hand tremor.